1998
DOI: 10.1007/s004210050329
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiological effects on exercise performance and selected physiological responses

Abstract: Previous studies investigating the impact of circadian rhythms on physiological variables during exercise have yielded conflicting results. The purpose of the present investigation was to examine maximal aerobic exercise performance, as well as the physiological and psychophysiological responses to exercise, at four different intervals (0800 hours, 1200 hours, 1600 hours, and 2000 hours) within the segment of the 24-h day in which strenuous physical activity is typically performed. Ten physically fit, but untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
51
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 27 publications
(52 reference statements)
15
51
2
1
Order By: Relevance
“…The relations between physical exercise and chronotype are still controversial, since workout performance is a result of many variables, including day shift (12)(13)(14)(15). A previous study (16) did not find differences in responses to exercise between morning and evening types; however, another investigation demonstrated that evening individuals had a higher energetic arousal in the evening than in the morning (17).…”
Section: Introductionmentioning
confidence: 82%
“…The relations between physical exercise and chronotype are still controversial, since workout performance is a result of many variables, including day shift (12)(13)(14)(15). A previous study (16) did not find differences in responses to exercise between morning and evening types; however, another investigation demonstrated that evening individuals had a higher energetic arousal in the evening than in the morning (17).…”
Section: Introductionmentioning
confidence: 82%
“…There are also large discrepancies between studies that focused on circadian maximal oxygen uptake patterns. Some studies concluded that this variable was stable throughout the day, [10][11][12][13] while others 14 demonstrated a 4.2% diurnal variation in this variable. Both day-to-day biological variability 10,11 and technical errors in oxygen uptake measurements could mask possible circadian fluctuations in maximal oxygen uptake, submit your manuscript | www.dovepress.com…”
Section: Introductionmentioning
confidence: 99%
“…The authors also hypothesized that an elevated muscle temperature increased the ATP turnover rate associated with exercise, and/or changes in the aerobic/anaerobic contribution to ATP resynthesis (Febbraio et al, 1996). Moreover, rectal and muscle temperature have shown lowest values in morning hours, and to progressively increase towards afternoon and evening hours (Deschenes et al, 1998;Reilly and Brooks, 1990). Hence in these studies, the lower early morning muscle peak torque values could be partly explained by muscle temperature at this TOD.…”
Section: Discussionmentioning
confidence: 85%